Social interactionism in the EFL writing class - Pico, María Lelia (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Social interactionism is a Vygotskyan approach to educational psychology which emphasizes the essential role of learners in constructing their own knowledge and understanding while learning foreign languages by means of the interaction and negotiation of meanings in communicative situations. The aims of this paper are to reflect upon our role as teachers to scaffold our students’ learning and to show how such scaffolding may be applied in EFL writing classes of different genres and how it is altered during exams.